Pengaruh Jumlah Tempat Wisata Baru, Pajak Hotel dan Pajak Restoran Terhadap Pendapatan Asli Daerah di Kabupaten Gunungkidul Tahun 2012-2016 - Randi Junior (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to determine the effect of the number of new tourist attractions, Hotel Tax and Restaurant Tax on Local Revenue Gunungkidul Regency. Population in this research is Report of the Number of new tourist attractions Data, Details of Hotel Tax Report, Restaurant Tax, and Local Original Revenue 2012-2016 period Gunungkidul Regency. period. The sampling technique used purposive sampling technique. The data in this research will be tested using statistical test, classic assumption test, and analyzed using multiple regression analysis. The results showed that the influence of the number of new tourist attractions, hotel taxes and restaurant tax simultaneously have a positive and significant impact on local revenue With F count > F table that is equal to 139,205 > 2,77 with a significance equal to 0,000 < 0,05. In T test the influence of the Number of new tourist attractions partially has no effect and not significant to the original revenue area, with t count < t table of 1,264 < 2,003 with a significance value of 0.211> 0.05. While the influence of hotel tax partially has no effect and not significant to the original revenue area, with t count < t table equal to -0.281 < 2.003 with a significance value of 0.780 > 0.05. While the influence of restaurant tax partially have a positive and significant effect on the local revenue, with t count > t table of 10.067 > 2,003 with a significance value of 0.000 > 0.05. While the influence of restaurant tax partially have a positive and significant effect on the local revenue, with t count > t table of 10.067 > 2,003 with a significance value of 0.000 < 0.05. While in the coefficient of determination test, R Square has a value of 0.875 which means the influence of the number of new tourist attractions, hotel taxes, restaurant taxes of 87.5% against local original revenue, while 12.5% influenced by other variables outside the research Keywords: Number of New Tourist Places, Hotel Tax, Restaurant Tax, Local Revenue.